(untitled) - Cox, Brad J. (Reading, Mass., 1991)
The first book published that fully describes object-oriented programming in an accessible manner for a wide range of readers. This new second edition covers the changes that have occurred in Objective C version 4.0, the newest release, and the tools that assist in developing object-oriented software.
Keywords: Lập trình hướng đối tượng (Khoa học máy tính),Object-oriented programming (Computer science)